The Influence of Gamification Learning Model with Wordwall Assistance on Conceptual Understanding of the Material on the Properties and Changes in the Form of Objects at SD Negeri 1 Bubusan - Safitri, Devi; Ramadhani, Erfan; Lubis, Patricia Hotma Minar (Jurnal Inovasi Pendidikan Dasar, 2025)
Low conceptual understanding among elementary students regarding phase changes in science lessons remains a challenge, mainly due to monotonous and less innovative teaching methods. This study aims to examine the effect of gamification-based learning assisted by Wordwall on improving students' conceptual understanding. A quantitative approach with a pre-experimental one-group pretest-posttest design was used. The instrument consisted of 15 multiple-choice questions validated by experts. The data were analyzed using normality test, homogeneity test, paired sample t-test, and N-Gain, assisted by SPSS version 30. The results show an increase in the average score from 76.27 (pretest) to 89.23 (posttest), with a significant value of 0.001 (< 0.05). The average N-Gain score was 0.5014, indicating a moderate improvement. These findings indicate that gamification learning supported by Wordwall significantly enhances students' conceptual understanding. The integration of Wordwall into gamified instruction makes science learning more interactive, enjoyable, and meaningful for elementary students.